Suspended sediment distribution pattern using remote sensing techniques in the Sambas River of Sambas Regency - Putri, Tiara Nusa; Putra, Yoga Satria; Risko, Risko; Muhardi, Muhardi; Adriat, Riza (Universitas Malikussaleh, 2023)
The Sambas River is part of the watershed of Sambas River which covers 71.03% of the total area of Sambas Regency. This river exhibits a mixed tidal regime with a tendency towards a double daily tide, which can cause sedimentation. Monitoring of this sedimentation can be conducted using remote sensing methods. The aim of this research is to analyze the concentration of suspended sediments based on direct measurements and appropriate algorithm processing. The data processing results from satellite images in 2022 using the Budhiman, Nurandani, and Lestari algorithms have a similar range of values to the direct measurements, ranging from 72 mg/L to 84 mg/L, although there are some data points that fall outside this range. However, the Budhiman algorithm demonstrates the best correlation with the direct measurements. The processed satellite data shows fluctuating values, indicating fluctuations in suspended sediment concentrations. Based on the conducted research, it is evident that the distribution pattern of suspended sediments in a river system can be analyzed using remote sensing techniques.Keywords: Remote Sensing; Suspended Sediment; Watershed